Patterns of Silent Reading Rate and Comprehension as a Function of Developmental Status, Genre, and Text Position. Issue 8 (17th November 2019) - Hayden, Emily; Hiebert, Elfrieda H.; Trainin, Guy
Abstract : This study examined how comprehension-based silent reading rate (CBSRR) is affected by grade, genre, and text position. Second and fourth graders read 2 grade-specific passages (one narrative, one informational) in 4 sections, each followed by 4 comprehension questions. Analyses of rate with a criterion level of comprehension showed higher performances on informational than narrative texts and better performances as students moved through sections of a text. Percentages of students attaining CBSRR decreased across the four sections of both genres and at both grade levels. Implications of findings are discussed and question are raised about text complexity and silent reading patterns.